Pictures of Hollis Woods - Giff, Patricia Reilly (New York : Scholastic, 2002)
A troublesome twelve-year-old orphan, staying with an elderly artists who needs her, remembers the only other time she was happy in a foster home, with a family that truly seemed to care about her.
Author of the Honor Book Lily's Crossing.
Keywords: Family life -- Fiction; Orphans -- Fiction; New York -- Fiction